A Comparative Policy Analysis of Education Systems and TVET Teacher Competencies in Indonesia and Malaysia - Thomas, Fendy; Noviandani, Pradika; Munawwiroh, Anis; Ismail, Muhammad Iqbal Al-Banna (International Journal of Ethno-Sciences and Education Research, 2026)
Educational systems and the competence of Technical and Vocational Education and Training (TVET) teachers play a crucial role in shaping the quality of human resources and national competitiveness. This study aims to comparatively analyze the education systems and TVET teacher competencies in Indonesia and Malaysia, two neighboring countries with similar cultural backgrounds but different educational governance and policy orientations. The study adopts a qualitative descriptive approach based on document analysis of laws, regulations, policy reports, and relevant literature related to national education systems and TVET teacher development in both countries. The findings indicate that Indonesia and Malaysia differ significantly in terms of educational structure, governance, funding mechanisms, and curriculum implementation, particularly at the secondary and vocational education levels. Malaysia demonstrates a more centralized and systematically evaluated education policy framework, supported by higher public investment in education. In contrast, Indonesia faces challenges related to educational quality, equity, and consistency in policy implementation. At the TVET level, both countries encounter similar issues, especially regarding teacher quality, uneven distribution of vocational teachers, and limited industry experience among educators. In Indonesia, the Professional Teacher Education Program (PPG) is expected to address shortages and improve the quality of vocational teachers. Meanwhile, Malaysia emphasizes the Modern Apprenticeship or dual system to enhance teachers’ industry exposure and practical competence. Despite differences in terminology, both countries recognize four essential domains of TVET teacher competence: pedagogical, professional, personal, and social or communication competence. The study concludes that strengthening industry collaboration and continuous professional development is essential to improving TVET teacher competence and aligning vocational education outcomes with labor market needs.